Robotics: Science and Systems IX 2013
DOI: 10.15607/rss.2013.ix.050
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Estimation of Measurement Bias in Three-Dimensional Field Sensors with Angular Rate Sensors: Theory and Comparative Experimental Evaluation

Abstract: Abstract-Three-axis magnetometers and three-axis accelerometers are widely used sensors for attitude estimation, yet their accuracy is limited by sensor measurement bias. This paper reports a novel methodology for estimating the sensor bias of three-axis field sensors (e.g. magnetometers and accelerometers). Our approach employs three-axis angular velocity measurements from an angular-rate gyroscope to estimate the three-axis field sensor measurement bias that, when properly calibrated, can significantly impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…We note that unlike most previous studies of field sensor bias estimation, the present study reports a comprehensive comparison of the performance of the proposed novel approaches to the performance of several previously reported approaches. Parts of this study were preliminarily reported in [2]. The present paper includes several additional novel theoretical and experimental contributions that have not been previously reported.…”
Section: Introductionmentioning
confidence: 78%
“…We note that unlike most previous studies of field sensor bias estimation, the present study reports a comprehensive comparison of the performance of the proposed novel approaches to the performance of several previously reported approaches. Parts of this study were preliminarily reported in [2]. The present paper includes several additional novel theoretical and experimental contributions that have not been previously reported.…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, data from the gyroscope is hereby omitted. In [15] on the other hand, the problem is reformulated in terms of the change in orientation, allowing for direct use of the gyroscope data.…”
Section: Related Workmentioning
confidence: 99%
“…Since bias errors are known to drift over time, continuously updating and subtracting this bias error from a measurement can improve performance. Three angular-rate aided estimators [46] improved bias estimation over previous methods of the TWOSTEP [2] and the attitude-independent EKF [10]. Others have improved performance by using an EKF to estimate bias and scale factor errors for both accelerometers and gyroscopes after a calibration procedure [5].…”
Section: Navigation With Inertial Measurement Units (Imu)mentioning
confidence: 99%